Holding Sweden hostage: firearm-related violence - Ardavan Khoshnood (Oxford University Press, 2019)
Swedish as well as foreign publications have reported a sharp increase in firearm-related violence in Sweden. None of these publications, however, combined official statistics from the Swedish police, the National Council for Crime Prevention (NCCP), and the National Board of Health and Welfare (NBHW), to study firearm-related violence in the last 2 years: 2016-2017. The results of this study show that firearm-related violence in Sweden has greatly increased compared to other Scandinavian countries, especially in recent years. This is probably the reason for the increase in the rate of deadly violence. Further, the increasing number of gangs and criminal networks, as well as the high inflow of illegal firearms to Sweden, is believed to have contributed to the disturbing increase of firearm-related violence in the country. Although Sweden is one of the most democratic and freest countries in the world, and has some of the world's strictest gun laws, the country still faces significant firearm-related violence. This study not only reveals the increasing rate of firearm-related violence in Sweden, but also shows that Sweden is in dire need of additional policies to combat the illegal flow of firearms and to curb gang criminality.